UPAYA MENINGKATKAN MOTIVASI BELAJAR DAN KREATIFITAS ANAK-ANAK DI PEMUKIMAN PEMULUNG DESA CIKETING DI ERA PANDEMI COVID-19 - RAISYA PUSPA SEPTIANI (BALANCING: Accountancy Journal, 2021)
COVID-19 has become an epidemic, so governments in all countries have implemented lockdown or quarantine measures. As long as the epidemic is not over and the situation is improving. Online learning will continue to apply. The role of parents in online learning is very much needed in motivating children at home to stay enthusiastic about learning. However, not all parents are able to play a role in the online learning system at home. Every family condition has its own problems and limitations. One of them is a family who lives in a scavenger settlement. Suggestions and infrastructure in ciketing scavenger settlements do not support children in online learning. This research used qualitative approach with descriptive methods. Research informants were selected by purposive sampling. Research data were collected by observation, interview and documentation study. Despite the limited facilities and infrastructure, children in ciketing scavenger settlements have high learning motivation and creativity. This can be seen from the activities of the children doing joint learning activities at the post located in the ciketing scavenger settlement